Ondine's Curse in Frontotemporal Dementia with Parkinsonism Linked to Chromosome 17 Caused by MAPT Variants. Issue 6 (24th June 2021) - Williams, Laura; Olszewska, Diana A.; Fearon, Conor; Magennis, Brian; McCarthy, Allan; Rowland, Lewis P.; Mayeux, Richard; Page, Rory; Fahn, Stanley; Beausang, Alan; Lynch, Tim
Abstract: Background: "Ondine's curse" or central hypoventilation, induces an apparently spontaneous failure of automatic respiratory drive, henceforth necessitating a conscious effort to breathe and sleep induced hypoventilation. It is typically seen in congenital central hypoventilation syndrome, but may be acquired. Objectives: To highlight Ondine's curse as part of frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP‐17) secondary to microtubule associated protein tau ( MAPT ) variants. Methods: We describe the clinical and neuropathological findings in two patients with fatal Ondine's curse associated with FTDP‐17 and secondary to MAPT variants (FTDP‐17t). We discuss neuroanatomical correlates. We review two prior reports of central hypoventilation associated with MAPT variants suggesting that Ondine's curse occurs uncommonly in FTDP‐17t. Results: Despite variants affecting different regions of MAPT and a degree of heterogeneity in pathological findings, the patients reviewed all experienced central hypoventilation during their disease course. Conclusion: Tauopathy should be considered in patients with adult‐onset Ondine's curse.